Analysis of the impact of an increase in goods and services tax (GST) in Singapore - Heng, Audrey Yue Li (2008)
To compare and contrast the impact of the 2003 increase in GST from 3% to 4% to that of 1994 introduction of GST at 3% on the consumers' viewpoint.